2016
DOI: 10.21613/gorm.2016.71
|View full text |Cite
|
Sign up to set email alerts
|

Altered Maternal Serum Dynamic Thiol-Disulfide Interchange Reactions in Pregnant Women with Gestational Diabetes Mellitus

Abstract: OBJECTIVE: We aimed to evaluate the alteration of dynamic thiol/disulfide homeostasis which basically shows the oxidative stress in body in pregnant women with gestational diabetes mellitus (GDM) by using a newly developed and automated analysis method. STUDY DESIGN: Study population consisted of body mass index and gestational age-matched pregnant women. Patients were subdivided into 3 groups based on their response to glucose challenge test (GCT) and oral glucose tolerance test (OGTT) results: (1) control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…There are several studies investigating association between TDH and gestational diabetes mellitus [94][95][96][97]. It has been demonstrated that NT and TT levels were found to be lower than control subjects and decreased NT levels have an increased risk of possible adverse perinatal outcomes [95].…”
Section: Obstetric and Gynecologic Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several studies investigating association between TDH and gestational diabetes mellitus [94][95][96][97]. It has been demonstrated that NT and TT levels were found to be lower than control subjects and decreased NT levels have an increased risk of possible adverse perinatal outcomes [95].…”
Section: Obstetric and Gynecologic Disordersmentioning
confidence: 99%
“…It has been demonstrated that NT and TT levels were found to be lower than control subjects and decreased NT levels have an increased risk of possible adverse perinatal outcomes [95]. It has been demonstrated that thiol levels were significantly lower whereas disulfide levels were significantly higher in patients with gestational diabetes mellitus compared with both pregnant women with impaired glucose tolerance and uncomplicated pregnant subjects [96]. Authors have investigated pregnant women with gestational diabetes mellitus, obese pregnant women and healthy pregnant women in terms of TDH of cord blood.…”
Section: Obstetric and Gynecologic Disordersmentioning
confidence: 99%
“…Lower levels of native thiol and total thiol were observed in patients with central serous chorioretinopathy and macular degeneration, as compared to control subjects 30,31 . Study showed that patients with gestational diabetes mellitus had significantly lower levels of thiol, and higher levels of disulfide, in comparison to both pregnant women with impaired glucose tolerance and uncomplicated pregnant subjects 32 . In a study assessing the thiol‐disulfide homeostasis in breast cancer, significant decrease in serum native thiol level was observed in breast cancer patients, along with an enhancement in serum disulfide level, suggesting a role of TDH in the pathogenesis of breast cancer 33 .…”
Section: Discussionmentioning
confidence: 78%
“…uncomplicated pregnant subjects. 32 In a study assessing the thioldisulfide homeostasis in breast cancer, significant decrease in serum native thiol level was observed in breast cancer patients, along with an enhancement in serum disulfide level, suggesting a role of TDH in the pathogenesis of breast cancer. 33 We showed that the disulfidptosis score was relatively higher in the epithelial and immune cells, compared to stromal cells in breast cancer.…”
Section: Discussionmentioning
confidence: 98%
“…OS has been examined in cases of fibroids, assisted reproduction, pregnancy loss, gestational diabetes, preeclampsia, IUGR, nuchal cord, and fetal death. [9][10][11][12][13][14][15] Thiols (RSH) are a class of organic compounds that can undergo oxidation reactions via oxidants and form disulfide bonds. Under conditions of OS, dynamic thiol/disulfide homeostasis is maintained, and it plays critical roles in antioxidant protection, detoxification, signal transduction, apoptosis, regulation of enzymatic activity, transcription factors, and cellular signaling mechanisms.…”
Section: Introductionmentioning
confidence: 99%